2003
DOI: 10.1029/2002jb002311
|View full text |Cite
|
Sign up to set email alerts
|

Magma supply dynamics at Westdahl volcano, Alaska, modeled from satellite radar interferometry

Abstract: [1] A group of satellite radar interferograms that span the time period from 1991 to 2000 shows that Westdahl volcano, Alaska, deflated during its 1991-1992 eruption and is reinflating at a rate that could produce another eruption within the next several years. The rates of inflation and deflation are approximated by exponential decay functions having time constants of about 6 years and a few days, respectively. This behavior is consistent with a deep, constant-pressure magma source connected to a shallow rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 42 publications
5
95
1
Order By: Relevance
“…It is difficult to distinguish between these two components, such that most of the models that are used to interpret deformation measurements can be classified into two end-members. The first set of models considers a magma reservoir surrounded by an elastic homogeneous medium and fed or drawn out through a hydraulic connection [Lu et al, 2003[Lu et al, , 2010Mastin et al, 2008], thus favoring a complex pressure evolution within the magma reservoir. In contrast, the second set of models usually considers a more simplistic pressure scenario, most often as a sudden pressurization that acts over a viscoelastic or poroelastic medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult to distinguish between these two components, such that most of the models that are used to interpret deformation measurements can be classified into two end-members. The first set of models considers a magma reservoir surrounded by an elastic homogeneous medium and fed or drawn out through a hydraulic connection [Lu et al, 2003[Lu et al, , 2010Mastin et al, 2008], thus favoring a complex pressure evolution within the magma reservoir. In contrast, the second set of models usually considers a more simplistic pressure scenario, most often as a sudden pressurization that acts over a viscoelastic or poroelastic medium.…”
Section: Discussionmentioning
confidence: 99%
“…However, these time constants are significantly smaller than those obtained for other basaltic volcanoes. Lengliné et al [2008] reported = 1.13 years for Kilauea Volcano and = 7.3 years for Mauna Loa Volcano, and Lu et al [2003] reported = 6 years for Westdahl Volcano. This difference can easily be explained either by a stronger hydraulic connection between the two reservoirs (a larger conduit with a smaller vertical extension) or by less viscous magma.…”
Section: Estimation Of the Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…8 is a compilation of selected recent works at volcanic areas subject to inflation larger than 5 km in diameter. We retrieve approximate diameters from previous geodetic studies (Amelung et al, 2000;Feigl et al, 2000;Lu et al, 2000Lu et al, , 2002aPritchard and Simons, 2002;Masterlark and Lu, 2004;Pedersen and Sigmundsson, 2004;Newman et al, 2006;Lundgren and Lu, 2006;Wicks et al, 2006) and add also the dimension of the Lazufre area for the four observed periods shown in Fig. 3.…”
Section: The Comparison To Other Inflation Caldera Systemsmentioning
confidence: 99%
“…Around the vent of the New Trident volcano in Alaska, a 7-9cm uplift was observed over a 2-year period by Lu et al (1997). Other case studies were reported by Rosen et al (1996), Amelung et al (2000), Lu et al (2003) and Furuya (2004). Due to its high degree of spatial coverage and completeness (spatial resolution of a few 10m over an image size of 100km × 100km), its cost-effectiveness and ability to penetrate clouds, the use of InSAR is certainly a beneficial option in complex and inaccessible terrain.…”
Section: Volcano Deformation Monitoringmentioning
confidence: 84%